Influences of dietary omega-3 fatty acids on haematologic and immunologic changes in rainbow trout milked regularly - Yonar, M. E.; Koprucu, K. (C M B Assoc, 2016)
In this study, it was examined the effects of dietary omega-3 fatty acids on the haematocrit (Ht), haemoglobin (Hb), mean corpuscular haemoglobin (MCH), total protein (TP) and total immunoglobulin (TI) values, erythrocyte (RBC) and leucocyte (WBC) counts, mean corpuscular volume (MCV), mean corpuscular haemoglobin concentration (MCHC), phagocytic index (PI) and nitroblue tetrazolium (NBT) activity in rainbow trout (Oncorhynchus mykiss) milked regularly. For this aim, one control and two experimental diets were prepared as isonitrogenous and isocaloric. Omega-3 fatty acid was not supplement to the control diet. However, the D1 and D2 diets included 1 and 3% omega-3 fatty acids, respectively. The Ht, Hb, RBC, WBC, MCV, MCH, MCHC, NBT, TP, TI and PI values of the rainbow trout fed the control diet were found significantly lower than these values in the fish fed the D2 and D1 diets at all sampling periods, too (P < 0.01). The highest levels for all these parameters were obtained from the fish fed the D2 diet at all sampling periods. These values in the rainbow trout fed the D2 diet were significantly higher than the values in the fish fed the D1 diet at all sampling periods (P < 0.01). However, the effect of sampling periods on these values in the fish fed the D1 and D2 diets was found insignificant (P > 0.01). In conclusion, the omega-3 fatty acid supplementation at 2% level to the diet can effectively support the haematological and immunological values in the rainbow trout under regular milking conditions, and ultimately protect the health.
Keywords: Rainbow trout; fatty acids; haematologic values; immune response; regular milking